Resting energy expenditure in critically ill patients: Evaluation methods and clinical applications - Sanches, Ana Cláudia Soncini [UNESP]; De Góes, Cassiana Regina [UNESP]; Bufarah, Marina Nogueira Berbel [UNESP]; Balbi, André Luiz [UNESP]; Ponce, Daniela [UNESP] (FapUNIFESP (SciELO), 2016)
Patients on intensive care present systemic, metabolic, and hormonal alterations that may adversely affect their nutritional condition and lead to fast and important depletion of lean mass and malnutrition. Several factors and medical conditions can influence the energy expenditure (EE) of critically ill patients, such as age, gender, surgery, serious infections, medications, ventilation modality, and organ dysfunction. Clinical conditions that can present with EE change include acute kidney injury, a complex disorder commonly seen in critically ill patients with manifestations that can range from minimum elevations in serum creatinine to renal failure requiring dialysis. The nutritional needs of this population are therefore complex, and determining the resting energy expenditure is essential to adjust the nutritional supply and to plan a proper diet, ensuring that energy requirements are met and avoiding complications associated with overfeeding and underfeeding. Several evaluation methods of EE in this population have been described, but all of them have limitations. Such methods include direct calorimetry, doubly labeled water, indirect calorimetry (IC), various predictive equations, and, more recently, the rule of thumb (kcal/kg of body weight). Currently, IC is considered the gold standard.
Keywords: Critically ill patient; Energy expenditure; Energy requirement; Indirect calorimetry